Pengaruh Penerapan Model Pembelajaran Teams-Games Tournament (TGT) terhadap Disposisi Matematis dan Hasil Belajar Matematika Peserta Didik - I Putu Eka Indrawan (Jurnal Pendidikan Matematika:Judika Education, 2021)
This study aims to determine the effect of the application of the Teams-Games Tournament (TGT) learning model on the mathematical disposition and learning outcomes of eighth grade students of SMP Negeri 3 Abiansemal in the 2020/2021 academic year. This type of research is classified as a Quasi Experiment with a Non Equivalent Posttest-Only Control Group Design research design. The population in this study were all students of class VIII SMP Negeri 3 Abiansemal as many as 12 classes with a total of 357 students. Two classes as samples with simple random sampling technique, namely class VIII G with 30 students as the experimental group and class VIII H with 30 students as the control group. The data obtained are quantitative data in the form of mathematical disposition scores (using a questionnaire) and mathematics learning outcomes (using an essay test). Analysis using MANOVA with the help of SPSS 23.0 for Windows. Based on the hypothesis test obtained: 1) there are differences in mathematical dispositions between students who follow the Teams-Games Tournament (TGT) learning model and students who follow the conventional learning model; 2) there are differences in mathematics learning outcomes between students who follow the Teams-Games Tournament (TGT) learning model and students who follow the conventional learning model; 3) there are simultaneous differences in mathematical dispositions and learning outcomes between students who follow the Teams-Games Tournament (TGT) learning model and students who follow the conventional learning model for class VIII of SMP Negeri 3 Abiansemal in the 2020/2021 school year. In conclusion, the results of the hypothesis test indicate that there is an effect of the application of the Teams-Games Tournament (TGT) learning model on the mathematical disposition and learning outcomes of eighth grade students of SMP Negeri 3 Abiansemal. Keywords: Teams-Games Tournament (TGT) Learning Model, Mathematical Disposition, Mathematics Learning Outcomes